2023
DOI: 10.3892/wasj.2023.187
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of miR‑146 expression in relation to malondialdehyde as a biomarker for oxidative damage in patients with breast cancer

Abstract: Breast cancer is the most common malignancy worldwide. The expression of microRNA (miRNA/miR)-146 has been shown to be related to breast cancer progression, and its expression in breast cancer cells has been investigated in the blood of patients. In the present study, the concentration of lipid peroxidation in blood cells was measured by detecting the level of malondialdehyde (MDA) to explore the level of oxidative cellular damage in the collected blood samples of breast cancer patients, alongside healthy wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…A number of studies have reported reduced total antioxidant capacity in different types of solid tumours [40], including those with HER2 + breast cancer [41]. Very recently, the oxidative damage has been investigated by malondialdehyde estimation in relation to miR-146a expression indicating their dual function to predict breast tumorigeneses [29]. The present findings seem to be consistent with other research which found reduced antioxidant capacity levels in cervical cancer patients [42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A number of studies have reported reduced total antioxidant capacity in different types of solid tumours [40], including those with HER2 + breast cancer [41]. Very recently, the oxidative damage has been investigated by malondialdehyde estimation in relation to miR-146a expression indicating their dual function to predict breast tumorigeneses [29]. The present findings seem to be consistent with other research which found reduced antioxidant capacity levels in cervical cancer patients [42].…”
Section: Discussionsupporting
confidence: 91%
“…However, no previous study has investigated its association with eNOS. Exploring the potential molecular biomarkers based on abnormal variation in gene expression to prognosticate survival of cancer patients has recently been our field of interest [3,[29][30][31][32]. This study was therefore set to investigate eNOS genetic polymorphism at the loci of 894G>T (rs1799983) and 786T>C (rs2070744) and to evaluate the contribution of different haplotypes variations on estimated serum levels of TAC of recruited individuals since genetic variants of eNOS gene may influence its role in breast carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MDA is a naturally occurring chemical compound that serves as a biomarker for oxidative stress when detected in blood plasma or tissues [10]. Several studies have provided evidence of elevated systemic MDA concentrations in individuals diagnosed with lung cancer [11] [12].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an immune response (anti-inflammatory) caused by type II myeloid cell and Th2 cell differentiation that leads to neuroprotection [22,23]. A number of molecular or immunological factors have been investigated to explore their potency to sensitize breast cancer cells [24][25][26][27] alongside other cancers [28,29] for therapeutic agents. Many researchers indicated the ability of DMF to inhibit NF-κB in many types of cancers and tumors [30,31].…”
Section: Introductionmentioning
confidence: 99%